Bridging the gap: induced pluripotent stem cell derived endothelial cells for 3D vascular assembly. (February 2017) - Macklin, Bria L; Gerecht, Sharon
Graphical abstract: Highlights: Endothelial cells can be efficiently derived from human pluripotent stem cells. Current approaches to study network assembly use adult stem and mature cells. Various biomaterials have been developed to facilitate network assembly. Complete characterization of endothelial cell derivatives needed for therapeutics. Abstract : As cardiovascular disease continues to take the lives of so many patients, it is paramount that scientists and engineers construct reliable, lasting vascular therapies. Stem cell therapies for cardiovascular disease have the potential to provide patient-specific treatments in order to heal or replace the diseased vasculature. This review highlights recent advances in endothelial cell (EC) differentiation from human pluripotent stem cells (hPSCs). We then describe in vitro studies focusing on understanding three-dimensional vascular assembly using human primary ECs and biomaterials developed for these systems. Finally, we highlight the unprecedented opportunity that hPSC- derived ECs provide to study human vascular development for fundamental understanding and toward the development of therapeutics.